Knowledge Repository Design to Improve Knowledge Management Process Capabilities: A Systematic Literature Review - Muhammad Farid Fadhlan; Dana Indra Sensuse (Ikatan Ahli Informatika Indonesia (IAII), 2022)
The role of technology in supporting knowledge management is very vital. The knowledge repository system is the foundation of knowledge management and its implementation. Knowledge sharing, discovery, and other knowledge processes will be more accessible through a proper knowledge repository system as an organizational knowledge base. This research explored various approaches employed by practitioners and researchers in designing a knowledge repository that allowed people to study and implement the knowledge repository as needed. A Systematic Literature Review (SLR) method proposed by Kitchenham was used to answer three research questions; (1) how is model knowledge storage in an organizational repository developed? (2) what tools can help create a knowledge repository? (3) What features should be present in a knowledge repository? The repository storage model was confirmed to be mainly represented in the ontology model. Furthermore, the technologies for creating knowledge were Protégé and Neo4j graph-based databases. In addition, features that were mostly applied in the knowledge repository system included data catalogs, search, API, knowledge management, visualization, rule-based and case-based reasoning.